Cone beam computed tomographic evaluation of styloid process: A retrospective study of 1000 patients - NAMDAR PEKİNER, FİLİZ MEDİHA (My University, 2017)
ABSTRACT Objective: The styloid process (SP) is a bony projection, located just anterior to the stylomastoid foramen, the normal length of which is approximately 20–30 mm. The length of SP when exceeds 30 mm it is said to “elongated.” The purpose of this retrospective study was to assess the prevalence of elongated SP (ESP) by cone beam computed tomography (CBCT) examination in Turkish subpopulation and its relation to gender and age. Materials and Methods: This study analyzed CBCT of 1000 patients who were randomly selected to participate and were aged from 14 to 78 years. Any radiograph with questionable SP was excluded from the study. The apparent length and thickness of the SP were measured by two dental and maxillofacial radiologists. The ESP was classified with radiographic appearance-based morphology of elongation. The data were analyzed with the IBM SPSS Statistics 20.0. Results: The mean age of patients was 42.49 ± 14.83 years. The length of SP was measured over 30 mm in 151 patients (15.1%). A total of 151 CBCT showed ESP, of which 87 (57.6%) were noticed in males and 64 (42.4%) in female patients. The length of right-sided SP ranged from 30.05 to 85.49 mm and left-sided SP from 30.14 to 83.72 mm. Conclusion: CBCT is a valuable diagnostic imaging tool which makes accurate length measurements. It is important for the clinicians to be aware of natural variations of the SP whose clinical importance is not well understood.
Cone beam computed tomographic evaluation of styloid process